2018
DOI: 10.1371/journal.pone.0201975
|View full text |Cite
|
Sign up to set email alerts
|

Processed eggshell membrane powder regulates cellular functions and increase MMP-activity important in early wound healing processes

Abstract: Avian eggshell membrane (ESM) is a natural biomaterial that has been used as an alternative natural bandage to cure wounds, and is available in large quantities from egg industries. We have previously demonstrated that processed eggshell membrane powder (PEP), aiming to be used in a low cost wound healing product, possesses anti-inflammatory properties. In this study, we further investigated effects of PEP on MMP activities in vitro (a dermal fibroblast cell culture system) and in vivo (a mouse skin wound heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 73 publications
1
26
0
2
Order By: Relevance
“…To evaluate if G. lucidum ethanol extract treatment could be helpful for skin care, from minor, superficial and basic skin injuries to more complicated pathological states such as ulcers or bedsores, pathologies which, in addition to cell proliferation, also required suitable cell migration [ 34 ], we evaluated whether the extract treatment influenced the expression and activity of proteins involved in cell migration. Furthermore, we reported an increase of the migration rate supported by activation of the matrix metalloproteinases (MMPs), specifically MMP-2 and MMP-9; the pathways downstream EGFR stimulation; and phospho-Src ( Figure 4 b), important factors for stimulation of cell migration and normal tissue remodelling [ 35 , 36 ]. These results were confirmed by the functional wound healing assay at all doses tested from 0.62 to 10 µg mL −1 , with 10 µg mL −1 being the most effective dose ( Figure 3 a,b).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate if G. lucidum ethanol extract treatment could be helpful for skin care, from minor, superficial and basic skin injuries to more complicated pathological states such as ulcers or bedsores, pathologies which, in addition to cell proliferation, also required suitable cell migration [ 34 ], we evaluated whether the extract treatment influenced the expression and activity of proteins involved in cell migration. Furthermore, we reported an increase of the migration rate supported by activation of the matrix metalloproteinases (MMPs), specifically MMP-2 and MMP-9; the pathways downstream EGFR stimulation; and phospho-Src ( Figure 4 b), important factors for stimulation of cell migration and normal tissue remodelling [ 35 , 36 ]. These results were confirmed by the functional wound healing assay at all doses tested from 0.62 to 10 µg mL −1 , with 10 µg mL −1 being the most effective dose ( Figure 3 a,b).…”
Section: Discussionmentioning
confidence: 99%
“…It can reduce knee pain and increase flexibility in joint and connective tissue disorder due to the presence of naturally occurring glycosaminoglycans and protein. Various studies also reported that ESM has a useful effect on cutaneous wounds in the early stages of healing . Yang et al 237.…”
Section: Second Generation Agricultural Wastes and Their Usesmentioning
confidence: 99%
“…Polycaprolactone (PCL) has good mechanical strength and, in combination with weak SEP, has a great potential as scaffold material and guided tissue regeneration barrier material. Processed eggshell membrane (PEP) also acts as skin wound healing activator 236. Processed eggshell membranes with its fibrous structure and collagen components enhances fibroblasts and keratinocytes, which migrate into the wound and start to proliferate.…”
Section: Second Generation Agricultural Wastes and Their Usesmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Egg shell membranes or egg shell membrane powder have been used as natural bandage for burns and injuries in traditional Asian medicine. Egg shell membrane powder and its carbohydrate constituents have been recently been demonstrated to exert anti-inflammatory effects 119,120 supporting their effectiveness.…”
Section: Yolk As Source Of Antibodiesmentioning
confidence: 99%